Saving by Understanding The Needs of People With Disabilities During Natural Disasters: A Scoping Review - Palenewen, Lucky Albertus (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
Natural disasters significantly increase the vulnerability of individuals with disabilities, resulting in a two to four times higher risk of death or injury compared to the general population. Research indicates they often have fewer resources, lower disaster preparedness, and are less likely to maintain household disaster kits, create evacuation plans, or participate in emergency drills. This scoping review aims to synthesize the essential needs of individuals with disabilities when confronted with natural disasters. The authors employed four databases—Wiley, ProQuest, Google Scholar, and Science Direct—to source relevant articles on the needs of individuals with disabilities in disaster scenarios. Following a quality appraisal per the PRISMA guidelines, twelve articles published between 2019 and 2024, accessible in full text and written in English, were selected from the various databases. The findings reveal that individuals with physical disabilities present diverse functional limitations that lead to distinct needs based on the type and level of disability. Among the primary necessities identified for individuals with disabilities in preparing for disasters are establishing social networks, access to pertinent information, 24-hour care services, providing evacuation equipment and tools, and education, training, and disaster response manuals. Addressing these needs is crucial for minimizing the adverse effects of natural disasters and facilitating a positive response and effective recovery for individuals with disabilities.